Nano-MOFs as targeted drug delivery agents to combat antibiotic-resistant bacterial infections. Issue 12 (2nd December 2020) - Ahmed, Saleh A.; Nur Hasan, Md.; Bagchi, Damayanti; Altass, Hatem M.; Morad, Moataz; Althagafi, Ismail I.; Hameed, Ahmed M.; Sayqal, Ali; Khder, Abd El Rahman S.; Asghar, Basim H.; Katouah, Hanadi A.; Pal, Samir Kumar
Abstract : The drug resistance of bacteria is a significant threat to human civilization while the action of antibiotics against drug-resistant bacteria is severely limited owing to the hydrophobic nature of drug molecules, which unquestionably inhibit its permanency for clinical applications. The antibacterial action of nanomaterials offers major modalities to combat drug resistance of bacteria. The current work reports the use of nano–metal-organic frameworks encapsulating drug molecules to enhance its antibacterial activity against model drug-resistant bacteria and biofilm of the bacteria. We have attached rifampicin (RF), a well-documented antituberculosis drug with tremendous pharmacological significance, into the pore surface of zeolitic imidazolate framework 8 (ZIF8) by a simple synthetic procedure. The synthesized ZIF8 has been characterized using the X-ray diffraction (XRD) method before and after drug encapsulation. The electron microscopic strategies such as scanning electron microscope and transmission electron microscope methods were performed to characterize the binding between ZIF8 and RF. We have also performed picosecond-resolved fluorescence spectroscopy to validate the formation of the ZIF8-RF nanohybrids (NHs). The drug release profile experiment demonstrates that ZIF8-RF depicts pH-responsive drug delivery and is ideal for targeting bacterial disease corresponding to its inherent acidic nature. Most remarkably, ZIF8-RF gives enhanced antibacterial activity against methicillin-resistant Staphylococcus aureus bacteria and also prompts entire damage of structurally robust bacterial biofilms. Overall, the present study depicts a detailed physical insight for manufactured antibiotic-encapsulated NHs presenting tremendous antimicrobial activity that can be beneficial for manifold practical applications.